1.
elimination 3x+y+z=−1, 4x+2y−z=6, x+y−3z=11
1.
elimination 3x+y+z=−1, 4x+2y−z=6, x+y−3z=11
2.
substitution x+2y−3z=−23, 4y+2z=−4, −x+y−z=−2
2.
substitution x+2y−3z=−23, 4y+2z=−4, −x+y−z=−2
3.
substitution x+2y−3z=−13, 4y+2z=2, −x+y−z=−2
3.
substitution x+2y−3z=−13, 4y+2z=2, −x+y−z=−2
4.
elimination x+2y−3z=−27, 4y+2z=10, −x+y−z=−4
4.
elimination x+2y−3z=−27, 4y+2z=10, −x+y−z=−4
5.
substitution x+y−z=3, 2x+y+z=5, 3x−2y+z=4
5.
substitution x+y−z=3, 2x+y+z=5, 3x−2y+z=4
6.
elimination x+y−z=0, x+2y−3z=−6, −2x+3y−4z=10
6.
elimination x+y−z=0, x+2y−3z=−6, −2x+3y−4z=10
7.
substitution x+y+z=24, x−2y+0=0, 2x+3y+1=12
7.
substitution x+y+z=24, x−2y+0=0, 2x+3y+1=12
8.
elimination 5x−2y+4z=9, x+y+z=6, 4x+3y+3z=3
8.
elimination 5x−2y+4z=9, x+y+z=6, 4x+3y+3z=3
9.
substitution x+2z=8, x−2y−2z=4, 2x+5y−6z=6
9.
substitution x+2z=8, x−2y−2z=4, 2x+5y−6z=6
10.
elimination y+z=−4, 5x+4y−16z=−6, x−y+5z=6
10.
elimination y+z=−4, 5x+4y−16z=−6, x−y+5z=6